Simulacija stroškov za izbor fleksibilnih proizvodnih sistemov - Bizjak, Franc (Les (Ljubljana), 1999)
Cost simulation can be an important instrument for choosing production system,which guarantees minimal costs. In the article possibilities and cost simulation model, which counts on productivness, flexibility and technology organisation, in dependence of costs, are described. This model enables choosing of the productional systems with which at equal other conditions, like quality and delivery times, we can choose the optimal production system.
Keywords: proizvodni sistemi; simulacija; stroški